Assessment of Community Empowerment Activities in Longido and Kiteto Districts, Tanzania - Bertha Erasto Losioki; Willie Tuimising' Rono (Interdisciplinary Journal of Education Research, 2020)
Tanzania, like other developing countries, strives to empower its people. However, the achievement of empowerment goals at individual and community is still a challenge in some areas. The purpose of this study was to assess community empowerment activities in Longido and Kiteto districts, Tanzania. The study involved 282 respondents (184 male and 98 female) aged 23 years and above.  The study adopted a qualitative approach, and a case study design was used. Data were collected through focused group discussions, in-depth interviews, documentary review and non-participant observation.  Content analysis was used to analyse data. The findings showed that the empowerment activities targeted social and economic aspects were gender-sensitive.  The activities were effective, and they brought real changes in people’s lives at individual and community levels.  The study concluded that there is a need for more training on the management of empowerment activities to ensure the efficiency and sustainability of the activities. The study, therefore, recommends capacity building through training, gender sensitivity in access to and control over the resources and improvement in health services.